Requirements definition and management practice to improve project outcomes - Yang, Li-Ren; Chen, Jieh-Haur; Huang, Chung-Fah (Journal of Civil Engineering and Management, 2012)
Poor project requirements definition and management (RDM) is one of the major causes of project failure. However, many organizations do not adequately manage a project’s requirements leading to a poor design basis. Thus, quality of requirements is critical to the success of any construction project. The primary purpose of this research was to investigate the mediating effect of requirements quality on the relationship between RDM practice and project performance. The second objective was to determine whether the impact of RDM practice on project performance was moderated by project characteristics. A three-phase approach was employed to investigate construction projects in the Taiwanese building industry. The testing supports a role for requirements quality as a partial mediator in the relationship between RDM practice and project performance. The findings also indicate that project characteristics have a moderating effect on the relationship between requirements quality and overall project performance. Reikalavimų apibrėžimas ir vadyba gerinant projekto rezultatus Santrauka. Prastai apibrėžti ir valdomi projekto reikalavimai – viena iš pagrindinių projekto nesėkmės priežasčių. Tačiau daug organizacijų neskiria pakankamai dėmesio projekto reikalavimų valdymui, todėl sukuriamas prastas projektavimo pagrindas. Taigi kokybės reikalavimai yra esminis sėkmės garantas bet kuriame statybų projekte. Pagrindinis šio tyrimo tikslas – išnagrinėti, kaip reikalavimų kokybė veikia jų apibrėžimo ir valdymo ryšį su projekto efektyvumu. Antrasis tikslas – nustatyti, ar projekto savybės mažina reikalavimų apibrėžimo ir valdymo poveikį projekto efektyvumui. Pritaikius trijų etapų metodą, išnagrinėti statybų projektai Taivano statybų sektoriuje. Bandymai patvirtino, kad reikalavimų kokybė iš dalies keičia jų apibrėžimo ir valdymo ryšį su projekto efektyvumu. Išvados taip pat rodo, kad projekto savybės riboja reikalavimų kokybės bendram projekto efektyvumui poveikį. Reikšminiai žodžiai: projekto reikalavimai, reikalavimų apibrėžimas ir valdymas, projekto efektyvumas, projekto savybės.